Excellent Long-Range Charge-Carrier Mobility in 2D Perovskites - Kober-Czerny, M; Motti, S G; Holzhey, P; Wenger, B; Lim, J; Herz, L M; Snaith, H J (University of Oxford, 2022)
The data was acquired as described in the 'Methods' section of the work. To analyse the data, python codes were run and are attached as well.